EVALUASI USABILITY WEBSITE STIE PUTRA BANGSA SEBAGAI MEDIA INFORMASI PERGURUAN TINGGI - Miftahul Huda (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
This study aims to evaluate the website interface on its usage convenince (usability). It also aims to providerecommendation based on the evaluation as an attempt to improve user acceptance level of the website. The object of this research is STIE Putra Bangsa website. The research is conducted in the application ofquantitative method in the approach of descriptive quantitative. Website is analized by the use of variables, namelydownload delay, navigation, interactivity, responsiveness, information, and user satisfaction. Simple random samplingis the sampling techique used in conducting this research with 94 respondents. The result of this research in the aspect of download delay it values the percentage of 75.80%. In the aspect ofnavigation it values the percentage of 72.94%. In the aspect of interactivity it values the percentage of 74.73%. In theaspect of responsiveness it values72.34%. In th aspect of information content it values 73.67%. In the aspect of usersatisfaction it values 72.96%. The above research results show that STIE Putra Bangsa is classified as good overall.